2016
DOI: 10.1016/j.mce.2016.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in vivo bioactivities of recombinant hypo- (FSH 21/18 ) and fully- (FSH 24 ) glycosylated human FSH glycoforms in Fshb null mice

Abstract: The hormone - specific FSHβ subunit of the human FSH heterodimer consists of N-linked glycans at Asn7 and Asn24 residues that are co-translationally attached early during subunit biosynthesis. Differences in the number of N-glycans (none, one or two) on the human FSHβ subunit contribute to macroheterogeneity in the FSH heterodimer. The resulting FSH glycoforms are termed hypo-glycosylated (FSH21/18, missing either an Asn24 or Asn7 N-glycan chain on the β - subunit, respectively) or fully glycosylated (FSH24, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 64 publications
6
48
0
Order By: Relevance
“…Interestingly, different data emerged from male FSHB null mice, where hFSH 21 /hFSH 18 promoted the increase of testicular weight more efficiently than the fully glycosylated FSH 24 , correlating with testis tubule size and the number of germ cells per tubule. In Sertoli cells of these animals, less glycosylated FSH promoted significantly higher expression levels of target genes and activation of proliferation markers than hFSH 24 [65]. Taken together, these data are suggestive of a relevant physiological impact of FSH glycoforms, even though this impact is likely to be sex-specific.…”
Section: Fsh In Therapymentioning
confidence: 73%
See 1 more Smart Citation
“…Interestingly, different data emerged from male FSHB null mice, where hFSH 21 /hFSH 18 promoted the increase of testicular weight more efficiently than the fully glycosylated FSH 24 , correlating with testis tubule size and the number of germ cells per tubule. In Sertoli cells of these animals, less glycosylated FSH promoted significantly higher expression levels of target genes and activation of proliferation markers than hFSH 24 [65]. Taken together, these data are suggestive of a relevant physiological impact of FSH glycoforms, even though this impact is likely to be sex-specific.…”
Section: Fsh In Therapymentioning
confidence: 73%
“…However, in vivo studies have only partially confirmed what was found in vitro; female FSHβ-encoding gene (FSHB) null mice injected with different doses of hFSH 21 /hFSH 18 or hFSH 24 had higher estradiol production with less glycosylated forms. These two glycoforms also impact on specific subsets of FSH-responsive genes, but no different activation of PKA, CREB, p38 MAPK, ERK and AKT were found, as well as ovarian weight gain, between less and fully glycosylated FSH [65,66]. These experiments suggest that the biased activity of FSH variants observed in vitro is likely attenuated in vivo.…”
Section: Fsh In Therapymentioning
confidence: 76%
“…with different doses of FSH glycoforms separately and at different times postinjection, ovaries were collected for subsequent selected gene expression analysis by quantitative real-time PCR. In these studies, hypo-glycosylated FSH 21/18 elicited in vivo bioactivity comparable to that of FSH 24 ; however, these analyses also indicated that differences exist between FSH 21/18 and FSH 24 glycoforms in inducing a unique subset of FSH-responsive genes ( 32 ). Second, to assess the upstream signaling pathways which control FSH-induced gene expression, immunofluorescence analysis was performed on ovarian sections obtained from Fshb null female mice injected with FSH 21/18 and FSH 24 glycoforms using p-CREB and p-PKA substrate antibodies.…”
Section: Genetic Models To Study the Physiology Of Fsh Glycoformsmentioning
confidence: 88%
“…This led to the concern that we were studying a physiologically irrelevant glycoform. However, subsequent demonstration of significant biological activity differences between other pituitary and recombinant FSH glycoform preparations eliminated this concern ( 18 , 31 , 32 ).…”
Section: Fsh Glycosylation Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation